2019
DOI: 10.1140/epjc/s10052-019-6687-6
|View full text |Cite
|
Sign up to set email alerts
|

Scalar perturbations and quasi-normal modes of a nonlinear magnetic-charged black hole surrounded by quintessence

Abstract: We study scalar perturbations and quasinormal modes of a nonlinear magnetic charged black hole surrounded by quintessence. Time evolution of scalar perturbations is studied for different parameters associated with the black hole solution. We also study the reflection and transmission coefficients along with absorption cross-section for the considered black hole spacetime. It was shown that the real part of quasinormal frequency increases with increase in nonlinear magnetic charge while the module of the imagin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 101 publications
1
12
0
Order By: Relevance
“…An increase in Q leads to the reduction of absorption probability (Figure 3) which is also consistent with the literature [32]. It is found that the greybody factor gets suppressed for larger values of α in comparison with [21] whereas the higher modes of rotation parameter show a substantial increase in the emission rate of massless scalar particles. For the orbital angular momentum, partial wave with smaller values reduce the greybody factor as for the rotating BH [33].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An increase in Q leads to the reduction of absorption probability (Figure 3) which is also consistent with the literature [32]. It is found that the greybody factor gets suppressed for larger values of α in comparison with [21] whereas the higher modes of rotation parameter show a substantial increase in the emission rate of massless scalar particles. For the orbital angular momentum, partial wave with smaller values reduce the greybody factor as for the rotating BH [33].…”
Section: Discussionsupporting
confidence: 89%
“…Saleh et al [20] studied the quasinormal modes as well as Hawking radiation for quintessential RN BH. Chakrabarty et al [21] analyzed the quasinormal modes as well as greybody factor for the emission of scalar particles around a nonlinear magnetic-charged BH surrounded by quintessence.…”
Section: Introductionmentioning
confidence: 99%
“…In Table I, we provide the ISCO radius obtained by solving Eqs. (19) and (22) numerically for different values of perfect fluid dark matter parameter α and magnetic charge parameter λ in the case of fixed black hole magnetic charge parameter g. The behavior of the results tabulated in Table I is also reflected in Fig. 11.…”
Section: Magnetically Charged Particle Motion Around Bardeen Blamentioning
confidence: 84%
“…Particularly, Kiselev has obtained a black hole solution surrounded by quintessence [18] and its rotational analogue obtained in [19]. The properties of black holes surrounded by quintessence have been studied in [20][21][22][23]. Authors of Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the quintessence, some exact black hole solutions were gotten and the thermodynamic properties were discussed [44][45][46][47][48][49][50][51]. In the study of the perturbations of the state parameter, Chakrabarty et al found that the perturbations with high value the parameter are unstable [52]. In axisymmetric black holes, the quintessence-like matter changes the shape of the black hole shadow [53].…”
Section: Introductionmentioning
confidence: 99%